Intelligent decision technologies : proceedings of the 7th KES International Conference on Intelligent Decision Technologies (KES-IDT 2015) /: proceedings of the 7th KES International Conference on Intelligent Decision Technologies (KES-IDT 2015). ([2015]) - Unknown
No abstract available